Modernidad y economía: crisis social y crisis epistémica - Reascos, Nelson (2006)
Modernity has produced great achievements for humanity. However, the process of development and consolidation of modernity as a spirit and as an ideal of life is not,nor has it been, homogeneous and universal as it was intended to be. On the contrary, modernity is human thinking and action full of ruptures, asymmetries, discontinuities and permanent change.